Corrosion Preventive Materials and Corrosion Testing - Dhawan, S. K. 1956-; Bhandari, Hema, 1980-; Ruhi, Gazala, 1978-; Bisht, Brij Mohan Singh (CRC Press LLC, 2020)
The book provides an extensive coverage of conjugated polymer based nano-composite coatings with advanced anti-corrosive properties. The book gives detailed explanation of corrosion testing methods and techniques to evaluate the corrosion resistance of the coatings. It includes elaborate discussion on classification of corrosion, electrochemistry of corrosion process, theories explaining the mechanism of corrosion and various corrosion testing standards. Electrochemical studies like open circuit potential (OCP) variation with time, potentiodynamic polarization, Electrochemical Impedance Spectroscopy (EIS) and accelerated corrosion testing are highlighted as important tools to extract information about the behavior of coatings under corrosive conditions. The book discusses epoxy-conjugated polymer based novel composite coating formulations, including aniline and o-toluidine, o-anisidine, phenetidine and pentafluoroaniline with appropriate fillers like SiO2, flyash, ZrO2 nanoparticles, and chitosan for the protection of metallic substrates. A general discussion on the self healing mechanism of epoxy-polypyrrole based biopolymer hybrid composite coatings is included in this book. This book provides a critical review on the conjugated polymer based composite coatings with superior corrosion resistance, good mechanical integrity, better adhesion properties and self healing ability under highly aggressive conditions which can be commercially used for the protection of metal substrates from corrosion.
Keywords: Corrosion resistant materials -- Testing.; Corrosion and anti-corrosives -- Testing.; Protective coatings -- Testing.; Conjugated polymers -- Testing.; Nanocomposites (Materials) -- Testing.; elektronické knihy; electronic books